Abordagem da geomorfologia em planos de manejo de parques nacionais: análise e perspectivas - Mariana Fonseca Mauro (2018)
National parks are regarded as territories of the highest importance for the conservation of the countrys natural resources, to which the plan of management presents itself as a planning and management tool, which aims at ordering the activities inside the unit starting from its zoning. The assessment stage must subsidize the creation of goals and actions taking into perspective the space and time dimensions in the conservation unit. We believe in geomorphologys relevance, in the aforementioned context, as possessive of integrative potential to understand the landscape in environmental studies. Therefore, the main goal in this research is to look into the way the geomorphological perspective has been developed in the assessment stage of Brazils National Parks management plans, as well as its contribution to the integrated understanding of the landscape, and its use as a subsidy in the planning stage. With this in mind, the trail was walked towards the reflection of possible ways to produce knowledge, under the optics of geomorphology, which can answer the problems and necessary challenges for conserving the target attributes and, finally, the question of what the necessary geomorphology is, different from that created through the perspective of inventories. The investigation process was developed starting from the selection and documental analysis of 37 national parks management plans under the criterion of time after the promulgation of the SNUC (National System of Conservation Areas) and The Methodological Guide for Planning National Park, Biological Reserve and Ecological Station, proposed in 2002. The analysis of how its done inferred, therefore, that (i) the geomorphological approach is restricted to the description, and approached without the delimitation of a problem, which greatly hurts the relevant analyses of management challenges; (ii) the methodological guide conveys minimal content that doesnt bring forth pertinent analyses of the plan of management; (iii) the creation of geomorphological assessments betrays the experience/intimacy of the researcher with one specific aspect of geomorphology; (iv) The elected and adopted space-and-time scale becomes a challenge to the production of applicable data; (v) the type of data in the assessment is related to the production of knowledge in a past time, lacking updates or incorporation of new data, information and methodological procedures; (vi) the geomorphological assessment, together with the other elements of the physical environment, helps recognizing relevant areas for the conservation of water resources and the parks scenic beauties; and, finally, that (vii) the restriction of database of RADAMBRASIL, and the lack of an a posteriori integrated geomorphological compartmentalization with the assessment stages other elements, strengthen its distance from the plan. Supported by these perceptions, we argue for a change of conception in doing geomorphology, committed to the object and goals of the conservation unit, where the scale transition, so dear to geography, should not be overlooked.